Low-cost high-safety porous silicon carbon material and preparation method thereof

Through direct vacuum sublimation of crude silicon and vapor deposition of porous carbon materials, combined with aniline solvent activation treatment, the problem of volume expansion and high cost of silicon-based negative electrode materials is solved, and the preparation of low-cost and high-safe porous silicon-carbon materials is realized. Improves the energy density and cycle stability of lithium-ion batteries.

CN119133425APending Publication Date: 2024-12-13XIANTAO HAIRONG NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411292762.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The energy density of traditional graphite negative electrode materials is insufficient, and the volume expansion of silicon-based negative electrode materials leads to damage to the electrode structure during charging and discharging. Existing solutions such as silane CVD technology have safety hazards and high costs, making it difficult to achieve industrialization.

Method used

The direct vacuum sublimation of crude silicon and porous carbon materials are used for vapor deposition. The activation treatment of aniline solvents and the adjustment of heat treatment conditions are ensured to ensure the safety and cost-effectiveness of silicon carbon materials, and the crystallization growth of silicon is inhibited to form porous with high circulation stability. Silicon-carbon material.

Benefits of technology

The preparation of low-cost and high-safe porous silicon carbon materials has been achieved, which significantly improves the energy density and cycle stability of lithium-ion batteries, reduces the production cost of silicon carbon materials, and inhibits volume expansion and improves electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005045092890000121
    Figure BDA0005045092890000121
  • Figure HDA0005045092910000011
    Figure HDA0005045092910000011
Patent Text Reader

Abstract

According to the low-cost and high-safety porous silicon carbon material and the preparation method thereof provided by the invention, crude silicon is directly sublimated in vacuum to serve as a silicon source for vapor deposition in the porous carbon material, so that the purity of the silicon source can be ensured, and the safety of the silicon carbon material in the preparation process is also greatly improved. And meanwhile, the cost of the crude silicon is low, so that the preparation cost of the whole silicon-carbon material is effectively controlled. Besides, the porous carbon material is activated, and heat treatment and cooling conditions during vapor deposition of crude silicon are adjusted, so that the crude silicon is uniformly and stably embedded into the porous carbon material in the vapor deposition process, crystal growth of silicon is inhibited, volume expansion of the porous silicon carbon material in the charging and discharging process is reduced, and the performance of the porous silicon carbon material is improved. The porous silicon carbon material with relatively good electrochemical performance and relatively high cycling stability is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery negative electrode materials, and in particular relates to a low-cost and high-safety porous silicon-carbon material and a preparation method thereof. Background Art

[0002] With the intensification of the global energy crisis and the increasing severity of environmental pollution, the development of new energy technologies has received unprecedented attention. Among the many new energy technologies, lithium-ion batteries have become the preferred power source in the fields of electric vehicles, portable electronic devices, etc. due to their high energy density, long life, and no memory effect. However, with the continuous advancement of technology, the energy density requirements for lithium-ion batteries are getting higher and higher, and traditional graphite negative electrode materials can no longer meet the needs of future development.

[0003] The theoretical capacity of graphite anode materials is only 372mAh / g. Although its actual application capacity has been close to the theoretical limit through various technical means, it is still difficult to meet the growing demand for energy density. Therefore, finding new anode materials to improve the energy density of lithium-ion batteries has become a hot topic in current research.

[0004] Silicon-based negative electrode materials have attracted much attention due to their high theoretical capacity (4200mAh / g). However, silicon reacts with lithium during the charge and discharge process to form lithium-silicon alloys, resulting in a volume expansion of more than 300%. This huge volume change will not only lead to the pulverization of the electrode material, but also cause damage to the electrode structure, thus seriously affecting the cycle performance and service life of the battery. Therefore, how to solve the problem of volume expansion of silicon-based negative electrode materials during the cycle process has become a key factor restricting its commercialization.

[0005] At present, the more common solution on the market is to use silane CVD (chemical vapor deposition) technology. Through the cracking of silane, silicon is deposited into the interior of the porous carbon material. The pore structure of the porous carbon material can provide sufficient space for the volume expansion of silicon during the charging and discharging process, thereby alleviating the problem of pulverization of silicon materials. However, this method has several significant disadvantages. First, silane is a highly flammable and explosive gas, and there are major safety hazards during use. Secondly, the production cost of silane is high, which directly leads to the poor economy of the entire production process. Finally, the equipment investment and operating costs of silane CVD technology are also relatively high. These factors have seriously restricted the industrial development of porous silicon-carbon materials.

[0006] Therefore, how to study and prepare a low-cost, highly safe and excellent electrochemical performance porous silicon-carbon material has become an important research topic in this field. Summary of the invention

[0007] In view of the problems in the prior art, the present invention discloses a low-cost and high-safety porous silicon-carbon material and a preparation method thereof. The present invention adopts crude silicon as a silicon source for vapor deposition inside the porous carbon material by direct vacuum sublimation, which not only ensures the purity of the silicon source, but also greatly improves the safety of the silicon-carbon material preparation process. At the same time, due to the low cost of crude silicon, the preparation cost of the entire silicon-carbon material is effectively controlled. In addition, the present invention also activates the porous carbon material, adjusts the heat treatment and cooling conditions during the crude silicon vapor deposition to make the crude silicon uniformly and stably embedded in the composite carbon material during the vapor deposition process, and at the same time inhibits the crystal growth of silicon, reduces the volume expansion of the porous silicon-carbon material during the charge and discharge process, and obtains a porous silicon-carbon material with better electrochemical performance and higher cycle stability.

[0008] The present invention is achieved through the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a low-cost and high-safety porous silicon-carbon material, the specific steps of which include:

[0010] S1: placing porous carbon particles into a reactor and adding an aniline solvent for pretreatment to obtain a pretreated porous carbon material;

[0011] S2: subjecting the pretreated porous carbon material and crude silicon described in S1 to high-temperature heat treatment in a high-temperature furnace after evacuation to obtain a porous silicon-carbon intermediate;

[0012] S3: cooling the high temperature furnace described in S2 at a rate greater than 40° C. / min, and then introducing a mixed gas of acetylene and nitrogen to prepare a porous silicon-carbon material;

[0013] The S2 medium-high temperature heat treatment includes a two-stage heating system: a first-stage heating and a second-stage step heating; the first-stage heating includes heating to a target temperature of 500-1000°C; the second-stage step heating includes heating from the target temperature of the first-stage heating to a final temperature of 1100-1600°C; during the second-stage step heating process, 80-200°C is used as a temperature step, and each temperature step is kept warm for more than 0.5h until the final temperature is reached.

[0014] The content W1 of the aniline solvent in S1 is selected from 1%≤W1≤10%; the mass ratio W2 of the crude silicon to the pretreated porous carbon material in S2 is selected from 0.5≤W2≤2.5; wherein W1 is the mass of the aniline solvent to the mass of the porous carbon particles.

[0015] As a further solution, the pretreatment temperature in S1 is selected from 200-300°C, the heating rate is selected from 5-10°C / min, and the insulation time is selected from 4-6h.

[0016] As a further solution, the first stage of heating includes heating to a target temperature preferably from 700-900°C, the heating rate is selected from 5-10°C / min, and the insulation time is selected from 2-3h; the second stage of step heating includes heating from the target temperature of the first stage of heating to a final temperature of 1200-1500°C; during the second stage of step heating, 100-150°C is used as a temperature step, and each temperature step is kept warm for more than 2 hours until the final temperature is reached; the heating rate is selected from 2-10°C / min, and the insulation time is selected from 4-6h.

[0017] As a further embodiment, the aniline solvent in S1 includes one or more of aniline, phenylethylamine, phenylenediamine, N-methylaniline, N-ethylaniline, N,N-dimethylaniline, and N,N-diethylaniline; preferably, the aniline solvent in S1 is preferably selected from phenylethylamine.

[0018] As a further solution, the specific surface area of ​​the porous carbon particles in S1 is selected from 1500-2500m 2 / g, the particle size is selected from 2-10μm, and the pore size is selected from 1-5nm.

[0019] As a further solution, the vacuum impurity removal method in S2 is to perform vacuum pumping operations 3-5 times.

[0020] As a further solution, the cooling method in S3 adopts a dual cooling method of air cooling and circulating water cooling; the cooling rate is selected from 60-120°C / min.

[0021] As a further solution, the high temperature furnace in S3 is cooled to a temperature of 500-600°C.

[0022] As a further solution, the introduction rate of the mixed gas in S3 is selected from 5-50 L / min; and the introduction time is selected from 4-10 h.

[0023] As a further solution, the mass ratio of acetylene to nitrogen in S3 is selected from 1:1.

[0024] As a further solution, the source of the crude silicon in S2 is selected from one or more of silicon ore, silicon sand, silica, and silicon alloy.

[0025] As a further solution, the reactor in S1 includes one or more of a reaction kettle, an autoclave, a stirring tank, a microwave reactor, and an ultrasonic reactor.

[0026] As a further solution, the S2 medium and high temperature furnace includes one or more of a rotary kiln, a tunnel kiln, a box furnace, a tubular furnace, and a hot air furnace.

[0027] In a second aspect, the present invention further provides a low-cost and high-safety porous silicon-carbon material, wherein the silicon-carbon material is obtained by the preparation method described in the first aspect.

[0028] In the third aspect, the present invention provides a sodium ion battery negative electrode plate made of low-cost and high-safety porous silicon-carbon material, wherein the negative electrode plate comprises the sodium ion battery negative electrode material prepared from the low-cost and high-safety porous silicon-carbon material of the second aspect of the present invention, a conductive agent and a binder.

[0029] The present invention does not particularly limit the type of conductive agent, as long as it has the function of enhancing the conductivity of the negative electrode and does not adversely affect the performance of the porous silicon-carbon material in preparing the negative electrode material of the sodium ion battery. Those skilled in the art can select the conductive agent commonly used in the art according to actual needs. As some specific examples, the conductive agent used to prepare the negative electrode plate can be selected from carbon blacks such as acetylene black and conductive carbon black, conductive polymers such as carbon nanotubes, graphene, graphite, polyaniline, polythiophene, tin oxide, zinc oxide and other metal oxide conductive agents and carbon nanofiber conductive agents, etc.

[0030] The present invention does not particularly limit the type of binder, as long as it has the function of enhancing the adhesion between the negative electrode active material particles and does not adversely affect the performance of the porous silicon-carbon material in preparing the negative electrode material for the sodium ion battery. Those skilled in the art can make a selection according to actual needs. As some specific examples, the binder used to prepare the negative electrode plate includes polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, polyimide, polystyrene sulfonic acid, polyacrylonitrile, polycarbonate or polyetherimide ketone, etc.

[0031] In a fourth aspect, the present invention provides a sodium ion battery, comprising the negative electrode sheet, the positive electrode sheet, the separator and the electrolyte described in the third aspect.

[0032] The characteristics and beneficial effects of the present invention are:

[0033] (1) The present invention adopts the method of vacuum sublimation of crude silicon to directly prepare porous silicon-carbon materials with porous carbon materials. The crude silicon materials with a wide range of sources are used, which significantly reduces the production cost and improves the safety of the silicon-carbon material preparation process, while maintaining the high electrochemical performance and cycle stability of the material.

[0034] (2) The present invention also activates the porous carbon material by using an aniline solvent, and adjusts the heat treatment and cooling conditions during the crude silicon vapor deposition process, thereby achieving uniform and stable embedding of the crude silicon into the composite carbon material during the vapor deposition process. In addition, the method effectively inhibits the crystal growth of silicon and reduces the volume expansion of the porous silicon-carbon material during the charge and discharge process, thereby preparing a porous silicon-carbon material with excellent electrochemical properties and high cycle stability.

[0035] (3) After preparing the porous silicon-carbon material, the present invention also introduces a mixed gas of acetylene and nitrogen, forming a uniform carbon atom deposition layer on the surface of the porous silicon-carbon material, further constraining the structure of the porous silicon-carbon material, preventing silicon from falling off, and inhibiting volume expansion; at the same time, the nitrogen also effectively prevents the oxidation of the silicon-carbon material and maintains the stability of the pore structure of the porous carbon material. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 This is the XRD diagram of the porous silicon carbon product. DETAILED DESCRIPTION

[0038] In order to facilitate the understanding of the present invention, the present invention will be described in more detail below, and embodiments of the present invention are given, but the scope of the present invention is not limited thereby.

[0039] In a first aspect, the present invention provides a method for preparing a low-cost and high-safety porous silicon-carbon material, the specific steps of which include:

[0040] S1: placing porous carbon particles into a reactor and adding an aniline solvent for pretreatment to obtain a pretreated porous carbon material;

[0041] S2: subjecting the pretreated porous carbon material and crude silicon described in S1 to high-temperature heat treatment in a high-temperature furnace after evacuation to obtain a porous silicon-carbon intermediate;

[0042] S3: cooling the high temperature furnace described in S2 at a rate greater than 40° C. / min, and then introducing a mixed gas of acetylene and nitrogen to prepare a porous silicon-carbon material;

[0043] The S2 medium-high temperature heat treatment includes a two-stage heating system: a first-stage heating and a second-stage step heating; the first-stage heating includes heating to a target temperature of 500-1000°C; the second-stage step heating includes heating from the target temperature of the first-stage heating to a final temperature of 1100-1600°C; during the second-stage step heating process, 80-200°C is used as a temperature step, and each temperature step is kept warm for more than 0.5h until the final temperature is reached.

[0044] The content W1 of the aniline solvent in S1 is selected from 1%≤W1≤10%; the mass ratio W2 of the crude silicon to the pretreated porous carbon material in S2 is selected from 0.5≤W2≤2.5; wherein W1 is the mass of the aniline solvent to the mass of the porous carbon particles.

[0045] The present invention uses crude silicon to be directly vacuum sublimated during the high-temperature heat treatment stage as a silicon source for vapor deposition inside the porous carbon material, which not only ensures the purity of the silicon source, but also greatly improves the safety of the silicon-carbon material preparation process. At the same time, due to the low cost of crude silicon, the preparation cost of the entire silicon-carbon material is effectively controlled.

[0046] In the process of preparing silicon-carbon material, the present invention first activates the porous carbon material using aniline solvent. On the one hand, the active amino groups on the aniline molecules form stable chemical bonds on the surface of the porous carbon material, thereby playing a role of stabilizing support for the porous structure of the carbon material, which is beneficial to the subsequent high-temperature treatment for silicon deposition and the maintenance of the stable pore structure of the structural carbon material during the final cooling. On the second hand, the aniline molecules can cause slight etching when used as activators to activate the porous carbon material. During the temperature pretreatment, nitrogen gas can be released to expand the pore structure of the carbon material and increase the pores, which is beneficial to the smooth embedding of silicon elements during the subsequent high-temperature treatment. At the same time, the nitrogen element plays a certain doping role on the porous carbon material, which is beneficial to enhance the adsorption sites on the surface of the porous carbon material. The π-π stacking effect between the benzene rings promotes the uniform arrangement of the pores of the carbon material, provides an orderly template for the deposition of silicon elements, helps to guide the silicon elements to be uniformly deposited inside the porous carbon material, enhances the binding force between the silicon elements and the carbon material, and forms a stable embedded silicon-carbon material. In addition, the present invention also adjusts and optimizes the pretreatment conditions and the content of aniline solvents during the activation treatment to ensure sufficient activation of the porous carbon material, which is beneficial to the uniform deposition and adsorption of silicon elements inside the carbon material during subsequent high-temperature treatment, and helps to inhibit the crystal growth of silicon elements and the volume expansion problem during the battery cycle.

[0047] Secondly, the present invention selects the appropriate mass ratio of crude silicon and porous carbon material activated by aniline solvents to ensure that the silicon material is evenly distributed inside the porous carbon material, while avoiding excessive deposition of silicon material, thereby effectively controlling the volume expansion of silicon-carbon material. During the high-temperature heat treatment process, the present invention also adopts a two-stage heating system to avoid uneven deposition of silicon elements due to direct heating, and volume expansion and rupture of silicon-carbon material pole pieces; the first stage of heating is to ensure that the aniline solvent is fully volatilized, and the pore structure of the pre-treated porous carbon material is stabilized; the second stage is to slowly step the temperature to promote the uniform high-temperature reaction of crude silicon inside the porous carbon material, avoid excessive crystal growth caused by uneven heating, and promote uniform and sufficient adsorption of silicon elements and porous carbon materials to form stable silicon-carbon materials. At the same time, the confinement effect of aniline solvents helps to further inhibit excessive aggregation and crystal expansion of silicon elements in the pore structure of carbon materials, avoiding problems such as unstable cycle of silicon-carbon material pole pieces and low battery capacity.

[0048] Finally, after the crude silicon is uniformly deposited into the porous carbon material activated by aniline solvents through vacuum sublimation, the present invention also uses a rapid cooling method at a rate greater than 40°C / min to cool the porous silicon-carbon material, further ensuring the structural stability of the silicon-carbon material and preventing the silicon element from excessively crystallizing at high temperatures inside the porous carbon material. Controlling the degree of cooling by rapid cooling is conducive to the introduction of a mixed gas of acetylene and nitrogen at an appropriate temperature, making it easier for the acetylene gas to decompose and produce carbon atoms that are deposited in the pores of the porous carbon material, forming a more uniform composite structure with the silicon element. At the same time, nitrogen is used to further stabilize the pore structure of the porous carbon material to prevent the silicon-carbon material from oxidizing at high temperatures; through this mixed gas treatment, the silicon-carbon material is subjected to a deeper binding effect, stabilizing its structure, inhibiting volume expansion, improving the cycle stability of the silicon-carbon material-prepared battery, and exerting its better electrochemical performance.

[0049] As a further solution, the pretreatment temperature in S1 is selected from 200-300°C, the heating rate is selected from 5-10°C / min, and the insulation time is selected from 4-6h; selecting appropriate pretreatment temperature, heating rate and insulation time can ensure a mild reaction between the porous carbon material and the aniline solvent, which is conducive to the full stabilization of the pore structure, while avoiding excessive defects in the pretreatment process, thereby providing a good foundation for subsequent high-temperature treatment. Inappropriate pretreatment temperature and insulation time will lead to uneven activation treatment, affect the activation effect, and are not conducive to widening the pore structure, thereby being not conducive to the subsequent embedding and stable adsorption of silicon elements. Too fast a heating rate may also cause thermal stress inside the carbon material, leading to the destruction of the pore structure. Therefore, selecting appropriate pretreatment conditions is conducive to the smooth embedding and adsorption of silicon elements in the subsequent process, further enhancing the battery cycle stability, and improving the battery rate and coulomb efficiency.

[0050] As a further solution, the first stage of heating includes heating to a target temperature preferably from 700-900°C, the heating rate is selected from 5-10°C / min, and the insulation time is selected from 2-3h; the second stage of step heating includes heating from the target temperature of the first stage heating to a final temperature of 1200-1500°C; during the second stage of step heating, 100-150°C is used as a temperature step, and each temperature step is kept warm for more than 2 hours until the final temperature is reached; the heating rate is selected from 2-10°C / min, and the insulation time is selected from 4-6h. The carefully designed heating system of the present invention helps to control the reaction rate, prevent thermal stress or uneven reaction of the material caused by too fast temperature change, avoid the formation of silicon crystals, thereby improving the structural stability of the material, and ensuring that the silicon element is evenly embedded in the internal structure of the porous carbon material. At the same time, the insulation time selected by the present invention is also conducive to the full removal of aniline solvents and improves the purity of silicon-carbon materials. If the heating rate is too fast, it will easily lead to uneven heating on the inside of the device, thus affecting the uniformity of silicon deposition inside the porous carbon material; excessive local silicon deposition will cause serious volume expansion of the silicon-carbon material electrode, posing a greater safety hazard and poor electrochemical performance.

[0051] As a further solution, the aniline solvent in S1 includes one or more of aniline, phenylethylamine, phenylenediamine, N-methylaniline, N-ethylaniline, N,N-dimethylaniline, and N,N-diethylaniline; preferably, the aniline solvent in S1 is preferably selected from phenylethylamine. Phenylethylamine has a higher boiling point and better thermal stability, can maintain stable chemical properties at high temperatures, is not easy to decompose and produce impurities, thereby providing a more uniform activation effect during the activation treatment. In addition, the ethylamine in the molecular structure of phenylethylamine has stronger chemical activity, which helps to form more stable chemical bonds on the surface of the porous carbon material, further enhancing the interface stability of the silicon-carbon material.

[0052] As a further solution, the specific surface area of ​​the porous carbon particles in S1 is selected from 1500-2500m 2 / g, the particle size is selected from 2-10μm, and the pore size is selected from 1-5nm. Porous carbon particles of this specification are conducive to full contact with aniline solvents, ensuring the uniformity of activation treatment, while providing sufficient surface area to promote uniform deposition of silicon. Porous carbon particles with high specific surface area can provide more adsorption sites, which helps silicon elements to form a stable mosaic structure inside the carbon material, thereby improving the overall electrochemical properties of the composite material. In addition, the appropriate particle size and pore size range help to ensure the conductivity and ion transfer efficiency of the material, and further optimize the charge and discharge and cycle stability performance of the battery.

[0053] As a further solution, the vacuum impurity removal method in S2 is to perform vacuum operation 3-5 times; this operation can ensure that the air and other impurity gases in the device are fully removed, thereby avoiding oxidation of the material and the generation of side reactions during subsequent high-temperature heat treatment, and improving the purity and stability of the final product.

[0054] As a further solution, the cooling method in S3 adopts a dual cooling method of air cooling and circulating water cooling; the cooling rate is selected from 60-120°C / min; this method absorbs and transfers heat through the flow of air and circulating water, can accurately control the cooling rate of the material, and achieve a rapid and uniform cooling effect, thereby reducing the generation of thermal stress in the material and the crystal growth of silicon particles caused by inappropriate cooling methods; resulting in uneven composite silicon-carbon materials, causing battery expansion and capacity attenuation, and other reductions in electrochemical performance.

[0055] As a further solution, the high temperature furnace in S3 is cooled to a temperature of 500-600°C. When maintained within this temperature range, it is not only beneficial to release the thermal stress inside the silicon-carbon material and stabilize the microstructure of the silicon-carbon material at high temperature; it is also beneficial for the acetylene gas to fully decompose to form a carbon coating layer when the subsequent mixed gas is introduced, further binding the silicon-carbon material and inhibiting its volume expansion during the charging and discharging process; at the same time, its carbon atom coating further enhances the conductivity of the silicon-carbon material.

[0056] As a further solution, the introduction rate of the mixed gas in S3 is selected from 5-50L / min; the introduction time is selected from 4-10h; when the mixed gas is introduced into the high-temperature furnace at an appropriate rate and time, it can ensure that the acetylene gas is fully decomposed in the pores of the porous carbon material to form a uniform carbon atom deposition layer. This carbon atom deposition layer not only helps to stabilize the structure of the silicon-carbon material, but also provides a good conductive channel during the charging and discharging process, thereby further improving the electrochemical performance of the battery. In addition, the introduction of nitrogen helps to prevent the silicon-carbon material from oxidizing at high temperatures, and also helps to stabilize the pore structure of the porous carbon material, ensuring that the material maintains good structural stability during the cyclic use process. If the gas introduction rate is too fast, acetylene gas may decompose rapidly on the surface of the material, forming an uneven carbon deposition layer, affecting the electrochemical properties of the material; and if the introduction time is too short, carbon atoms may not be sufficiently deposited and an effective protective layer cannot be formed. Therefore, choosing a suitable introduction rate and time is crucial for the preparation of high-performance silicon-carbon materials.

[0057] As a further solution, the mass ratio of acetylene and nitrogen in S3 is selected from 1:1; this ratio is conducive to the decomposition of acetylene gas at high temperature to form a carbon atom deposition layer, while nitrogen can effectively prevent oxidation of silicon-carbon materials and maintain the stability of the pore structure of the porous carbon material.

[0058] As a further solution, the source of the crude silicon in S2 is selected from one or more of silicon ore, silicon sand, silica stone, and silicon alloy; the crude silicon material is obtained by the above-mentioned multiple raw materials, which has the characteristics of low cost and wide source, thereby reducing the production cost of porous silicon-carbon materials.

[0059] As a further solution, the reactor in S1 includes one or more of a reaction kettle, an autoclave, a stirring tank, a microwave reactor, and an ultrasonic reactor;

[0060] As a further solution, the S2 medium and high temperature furnace includes one or more of a rotary kiln, a tunnel kiln, a box furnace, a tube furnace, and a hot air furnace;

[0061] In a second aspect, the present invention further provides a low-cost and high-safety porous silicon-carbon material, wherein the silicon-carbon material is obtained by the preparation method described in the first aspect.

[0062] In the third aspect, the present invention provides a sodium ion battery negative electrode plate made of low-cost and high-safety porous silicon-carbon material, wherein the negative electrode plate comprises the sodium ion battery negative electrode material prepared from the low-cost and high-safety porous silicon-carbon material of the second aspect of the present invention, a conductive agent and a binder.

[0063] The present invention does not particularly limit the type of conductive agent, as long as it has the function of enhancing the conductivity of the negative electrode and does not adversely affect the performance of the porous silicon-carbon material in preparing the negative electrode material of the sodium ion battery. Those skilled in the art can select the conductive agent commonly used in the art according to actual needs. As some specific examples, the conductive agent used to prepare the negative electrode plate can be selected from carbon blacks such as acetylene black and conductive carbon black, conductive polymers such as carbon nanotubes, graphene, graphite, polyaniline, polythiophene, tin oxide, zinc oxide and other metal oxide conductive agents and carbon nanofiber conductive agents, etc.

[0064] The present invention does not particularly limit the type of binder, as long as it has the function of enhancing the adhesion between the negative electrode active material particles and does not adversely affect the performance of the porous silicon-carbon material in preparing the negative electrode material for the sodium ion battery. Those skilled in the art can make a selection according to actual needs. As some specific examples, the binder used to prepare the negative electrode plate includes polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, polyimide, polystyrene sulfonic acid, polyacrylonitrile, polycarbonate or polyetherimide ketone, etc.

[0065] In a fourth aspect, the present invention provides a sodium ion battery, comprising the negative electrode sheet, the positive electrode sheet, the separator and the electrolyte described in the third aspect.

[0066] As a specific example of the implementation of the present invention, the detailed case is provided as follows:

[0067] Example 1

[0068] Take 100 grams of specific surface area of ​​2000m 2 / g, porous carbon particles with a particle size of 5μm and an average pore size of 3nm are used as starting materials. The porous carbon particles are sent to a reactor, a 4% by mass phenylethylamine solvent is added, the reactor is sealed, and the speed is set to 50Hz, and pretreatment is performed at 200°C, and the heating rate is controlled at 5°C / min. After reaching the pretreatment temperature, the temperature is maintained to continue the reaction for 4 hours. After the pretreatment is completed, it is naturally cooled to room temperature, and the porous carbon particles are taken out to obtain a pretreated porous carbon material;

[0069] Accurately weigh the coarse silicon particles and mix them evenly with the pretreated porous carbon material obtained in the above steps, and control the mass ratio of coarse silicon to the porous carbon material obtained by pretreatment to be 1:1; put the mixture into a rotary kiln, perform three vacuum operations, and then start high-temperature heat treatment. First, the first stage of heating is carried out, and the temperature is raised to 800°C at a rate of 8°C / min, and the temperature is maintained for 3 hours. Then enter the second stage of step heating, and heat at a rate of 3°C / min. Each time the temperature is increased by 100°C, the temperature is maintained for 3 hours until the temperature reaches 1400°C. Keep warm at 1400°C for 6 hours to complete the high-temperature heat treatment and obtain a porous silicon-carbon intermediate.

[0070] After the high-temperature heat treatment is completed, the high-temperature furnace is first cooled to 600°C by air cooling and circulating water cooling, and the cooling rate is controlled at 90°C / min. After the cooling is completed, a mixed gas of acetylene and nitrogen is introduced into the furnace at a rate of 10L / min for 8 hours. During the introduction of the mixed gas, the mass ratio of acetylene and nitrogen is maintained at 1:1. After the above steps, a porous silicon-carbon material is finally obtained.

[0071] Embodiment 2:

[0072] The same as Example 1, except that the porous carbon material is activated by using a phenylenediamine solvent.

[0073] Embodiment 3:

[0074] Same as Example 1, except that 8% by mass phenylethylamine solvent was added.

[0075] Embodiment 4:

[0076] Same as Example 1, except that a 2% by weight phenylethylamine solvent was added.

[0077] Embodiment 5:

[0078] The same as Example 1, except that the mass ratio of crude silicon to the porous carbon material obtained by pretreatment is controlled to be 45:55.

[0079] Embodiment 6:

[0080] The same as Example 1, except that the mass ratio of crude silicon to the porous carbon material obtained by pretreatment is controlled to be 55:45.

[0081] Embodiment 7:

[0082] The same as Example 1, except that after the high temperature heat treatment is started, the first stage of temperature increase is first performed, the temperature is increased to 700°C at a rate of 10°C / min, and the temperature is maintained for 3 hours. Then the second stage of step temperature increase is entered, the temperature is increased at a rate of 5°C / min, and the temperature is maintained for 3 hours every time the temperature is increased by 100°C, until the temperature reaches 1200°C. The temperature is kept at 1200°C for 6 hours to complete the high temperature heat treatment and obtain a porous silicon-carbon intermediate.

[0083] Embodiment 8:

[0084] The same as Example 1, except that the high temperature heat treatment is started, firstly, the first stage of temperature increase is carried out, the temperature is increased to 900°C at a rate of 5°C / min, and the temperature is maintained for 3 hours. Then, the second stage of step temperature increase is entered, the temperature is increased at a rate of 10°C / min, and the temperature is maintained for 3 hours every time the temperature is increased by 100°C, until the temperature reaches 1500°C. The temperature is kept at 1500°C for 6 hours to complete the high temperature heat treatment, and a porous silicon carbon intermediate is obtained.

[0085] Embodiment 9:

[0086] The same as Example 1, except that after the high-temperature heat treatment is completed, the high-temperature furnace is first cooled to 500° C. by air cooling and circulating water cooling, and the cooling rate is controlled at 120° C. / min.

[0087] Embodiment 10:

[0088] The same as Example 1, except that after the temperature was lowered, a mixed gas of acetylene and nitrogen was introduced into the furnace at a rate of 10 L / min for 5 hours.

[0089] Comparative Example 1

[0090] The same as Example 1, except that the porous carbon material is not activated by the phenylethylamine solvent.

[0091] Comparative Example 2

[0092] Same as Example 1, except that a phenylethylamine solvent having a mass content of 20% was added.

[0093] Comparative Example 3

[0094] The same as Example 1, except that the mass ratio of crude silicon to the porous carbon material obtained by pretreatment is controlled to be 1:5.

[0095] Comparative Example 4

[0096] The same as Example 1, except that the mass ratio of crude silicon to the porous carbon material obtained by pretreatment is controlled to be 5:1.

[0097] Comparative Example 5

[0098] The same as Example 1, except that after the high temperature heat treatment is started, the temperature is directly raised to 1400° C. at a rate of 8° C. / min. The temperature is kept at 1400° C. for 6 hours to complete the high temperature heat treatment and obtain a porous silicon-carbon intermediate.

[0099] Comparative Example 6

[0100] The same as Example 1, except that the high temperature heat treatment is started, firstly, the first stage of temperature increase is carried out, the temperature is increased to 400°C at a rate of 8°C / min, and the temperature is maintained for 3 hours. Then, the second stage of step temperature increase is entered, the temperature is increased at a rate of 3°C / min, and the temperature is maintained for 3 hours every time the temperature is increased by 100°C, until the temperature reaches 700°C. The temperature is kept at 700°C for 6 hours to complete the high temperature heat treatment, and a porous silicon carbon intermediate is obtained.

[0101] Comparative Example 7

[0102] The same as Example 1, except that the high temperature heat treatment is started, firstly the first stage of temperature increase is carried out, the temperature is increased to 1100°C at a rate of 8°C / min, and the temperature is maintained for 3 hours. Then the second stage of step temperature increase is entered, the temperature is increased at a rate of 3°C / min, and the temperature is maintained for 3 hours every time the temperature is increased by 100°C, until the temperature reaches 2000°C. The temperature is kept at 2000°C for 6 hours to complete the high temperature heat treatment, and a porous silicon carbon intermediate is obtained.

[0103] Comparative Example 8

[0104] The same as Example 1, except that after the high-temperature heat treatment is completed, the high-temperature furnace is first cooled to 600° C. by natural cooling.

[0105] Comparative Example 9

[0106] The same as Example 1, except that after the temperature reduction is completed, a mixed gas of acetylene and nitrogen is introduced into the furnace at a rate of 10 L / min for 1 hour.

[0107] Comparative Example 10

[0108] The same as Example 1, except that after the temperature was lowered, ethanol gas was introduced into the furnace at a rate of 10 L / min for 8 hours.

[0109] Specific test conditions and methods:

[0110] Preparation and testing of battery negative electrode: The prepared porous silicon-carbon material was mixed with graphite, CMC, SBR, and PAA in a ratio of 20:76:1:1:2 to make a negative electrode sheet, and its capacity and initial efficiency were tested. At the same time, the negative electrode material was combined with the NCM positive electrode material to make a battery, and a 0.33C / 0.33C charge and discharge cycle test was performed to record the expansion rate at different stages and the capacity retention rate at different cycle numbers.

[0111] Test method for inflation mean:

[0112] Measure the thickness h1 of the electrode when assembled, charge the assembled battery at 0.33C to 4.2V, disassemble and measure the thickness h2 of the electrode after full charge, and its expansion rate is (h2-h1) / h1. Test the expansion rates of the three groups of electrode sheets separately, and their average is the expansion mean.

[0113] Expansion ratio test method:

[0114] First, the average expansion value r1 of the negative electrode group after the silicon carbon and graphite are mixed near the furnace wall is measured, and then the average expansion value r2 of the negative electrode group after the silicon carbon and graphite are mixed near the furnace interior is measured. The expansion ratio is r1 / r2

[0115] Table 1

[0116]

[0117] It can be seen from Table 1 that the porous silicon-carbon materials prepared in Examples 1-10 of the present invention are significantly superior to the battery electrical performance of Comparative Examples 1-10 in terms of electrical performance, cycle stability and expansion control in the battery, and the expansion ratio close to 1:1 between the furnace wall and the furnace interior can reflect that the material can be evenly heated under the heating system of the present invention; this indicates that the method of preparing the porous silicon-carbon material by activating the porous carbon material and then performing vapor deposition by vacuum sublimation of crude silicon has a significant effect on inhibiting the expansion of the silicon-carbon negative electrode and improving the electrochemical performance and cycle stability of the battery.

[0118] It can be seen from Example 1 and Comparative Example 1 that the porous carbon material treated with aniline solvents has higher cycle stability, battery capacity and lower expansion mean when silicon is deposited. This is because the π-π stacking of the aniline solvents and the chemical bonding of the amino group and the carbon material stabilize the porous structure of the carbon material and widen the pore structure, which is conducive to guiding the silicon element to be smoothly embedded and evenly and stably composited with the carbon material, thereby reducing the interface resistance and promoting the ion transmission efficiency; and the confinement effect of the aniline material provides a strong mechanical stress for the porous structure, effectively inhibiting the volume expansion of the silicon element, thereby having a higher cycle stability.

[0119] It can be seen from Example 1 and Comparative Example 2 that when the amount of aniline solvent added is too much, it has a lower first-cycle coulombic efficiency and a higher expansion mean. This is because the addition of too many aniline molecules may cause excessive etching, destroy the pore structure of the carbon material, cause the silicon crystals to grow vigorously, and fail to maintain the structural stability of the carbon material, thereby failing to effectively inhibit the volume expansion of the battery and reducing the cycle stability performance; and the excessively added aniline molecules will also occupy the pore area, hinder the deposition path of the silicon element, thereby causing the ion transmission path to be blocked, and the coulombic efficiency and capacity of the battery cannot be well improved.

[0120] It can be seen from Example 1 and Comparative Examples 3 and 4 that an appropriate range of the ratio of porous carbon material to crude silicon can obtain better electrochemical performance. This is because the silicon element is fully and effectively deposited inside the porous carbon material. When the proportion of crude silicon added is too low, the capacity of the material is low; and when the proportion of crude silicon added is too high, too much silicon element cannot be completely compounded with the porous carbon material. The uncompounded silicon element is prone to volume expansion during the battery cycle, resulting in damage to the electrode structure, thereby affecting the battery's cycle stability.

[0121] It can be seen from Example 1 and Comparative Examples 5, 6, and 7 that the use of a secondary heating system and matching the appropriate temperature is more conducive to reducing the average expansion of the battery, improving the battery capacity and cycle stability performance; Comparative Example 5 adopts a direct heating system, and its expansion ratio close to the furnace wall and close to the furnace interior is significantly increased, and the cycle stability and battery coulomb efficiency and capacity are poor; this is because the direct heating method will cause uneven heating of the material, which is not conducive to the full sublimation of the crude silicon material into silicon element gas for deposition, and will cause insufficient silicon element that can be deposited in the gas phase to cause uneven composite silicon-carbon materials, thereby reducing the electrochemical performance of porous silicon-carbon materials. The heating temperature of Comparative Example 6 is too low, resulting in insufficient sublimation of crude silicon and uneven deposition of silicon elements, while the heating temperature of Comparative Example 7 is too high, which accelerates the crystallization growth rate of silicon elements during the deposition process, resulting in serious volume expansion, destroying the structural stability of the porous carbon material, and thus affecting the cycle performance of the battery. Example 1 uses a two-step heating system, in which the first step of heating fully removes the residual aniline solvent and avoids the influence of impurities. The second step-by-step heating ensures uniform heating inside the reaction device and promotes full sublimation and vapor deposition of crude silicon, thereby obtaining higher capacity, first-cycle coulombic efficiency and cycle stability; inhibits silicon crystal growth, thereby reducing the volume expansion of battery materials.

[0122] It can be seen from Example 1 and Comparative Example 8 that the expansion mean of the battery is larger when the temperature is lowered by natural cooling. This is because the cooling rate is slow, which easily causes excessive growth of silicon crystals, destroys the structural stability of the silicon-carbon material, and hinders the transmission channel of ions, resulting in reduced battery coulombic efficiency, capacity and cycle stability. However, Example 1 adopts a dual rapid cooling method of air cooling and water cooling, which can better control the degree of cooling, which is not only conducive to effectively inhibiting the excessive growth of silicon crystals and avoiding battery volume expansion; it is also conducive to introducing acetylene and nitrogen mixed gas at an appropriate temperature, fully and evenly coating the silicon-carbon material, and avoiding the silicon element from falling off during the cycle, thereby improving the cycle stability of the battery material, maintaining a stable capacity output, ensuring a stable and complete ion transmission channel, and improving the battery's coulombic efficiency.

[0123] By comparing Example 1 with Comparative Example 9, it can be seen that Example 1 has better cycle stability and better electrochemical performance. This is because when the amount of acetylene introduced is too low, it is not conducive to fully and tightly coating the porous silicon-carbon material, resulting in the silicon element easily falling off during the cycle, affecting the cycle stability of the battery and reducing the electrochemical performance of the battery. Example 1 ensures that a uniform and dense carbon coating layer is formed on the surface of the porous silicon-carbon material by controlling the introduction rate and time to introduce a suitable amount of acetylene, which not only ensures the stable embedding of the silicon element, but also maintains a good ion transmission channel, thereby achieving high cycle stability and excellent electrochemical performance of the battery.

[0124] By comparing Example 1 with Comparative Example 10, it can be seen that when ethanol gas is introduced into Comparative Example 10, the expansion mean of the battery is relatively high. This is because the ethanol gas cracking temperature is relatively high, resulting in the inability to effectively crack into carbon element at this temperature to be coated on the porous silicon-carbon surface, thereby affecting the electrochemical performance and cycle stability of the battery. The acetylene and nitrogen mixed gas used in Examples 1-10 has high stability at high temperatures and does not produce excessive decomposition products, thereby effectively avoiding the increase in internal pressure of the battery. At the same time, acetylene reacts with the surface of the porous silicon-carbon material at high temperatures to form a uniform and dense carbon coating layer, which further enhances the structural stability of the material and effectively inhibits the volume expansion of the silicon element, thereby improving the cycle stability and electrochemical performance of the battery.

[0125] It can be seen from Examples 1-10 and the contents of Table 1 that Example 1 has better electrochemical performance than Examples 2-9; its expansion mean is as low as 32%; it can be seen that the type of aniline solvent within the preferred range, as well as the heat treatment temperature and cooling treatment can obtain sufficient sublimation of the crude silicon material and uniformly and stably deposit it inside the porous carbon material, thereby improving the composite effect of the silicon-carbon material, and obtaining a suitable pore path to promote the smooth embedding of the silicon element, thereby improving the capacity, coulombic efficiency and other properties of the prepared porous silicon-carbon material, and the lower expansion mean ensures that the porous silicon-carbon material has higher cycle stability.

[0126] Depend on Figure 1 It can be seen that no obvious silicon peak (28.4°) is shown in the XRD pattern, indicating that the silicon deposited by this process has not crystallized and grown.

[0127] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a low-cost, high-safety porous silicon-carbon material, with specific steps include: S1: placing porous carbon particles into a reactor and adding an aniline solvent for pretreatment to obtain a pretreated porous carbon material; S2: subjecting the pretreated porous carbon material and crude silicon described in S1 to high temperature heat treatment in a high temperature furnace after evacuation to obtain a porous silicon-carbon intermediate; S3: cooling the high temperature furnace described in S2 at a rate greater than 40° C. / min, and then introducing a mixed gas of acetylene and nitrogen to prepare a porous silicon-carbon material; The S2 medium-high temperature heat treatment includes a two-stage heating system: a first-stage heating and a second-stage step heating; the first-stage heating includes heating to a target temperature of 500-1000°C; the second-stage step heating includes heating from the target temperature of the first-stage heating to a final temperature of 1100-1600°C; during the second-stage step heating process, 80-200°C is used as a temperature step, and each temperature step is kept for more than 0.5h until the final temperature is reached; The content of aniline solvent in S1 is W 1 Selected from 1% ≤ W 1 ≤10%; the mass ratio of the crude silicon in S2 to the pretreated porous carbon material W 2 Select from 0.5≤W 2 ≤2.5; where W 1 is the mass of aniline solvent to the mass of porous carbon particles.

2. The method for preparing the low-cost and high-safety porous silicon-carbon material according to claim 1, It is characterized in that In the S1, the pretreatment temperature is selected from 200-300°C, the heating rate is selected from 5-10°C / min, and the insulation time is selected from 4-6h.

3. The method for preparing the low-cost and high-safety porous silicon-carbon material according to claim 1, It is characterized in that The first stage of heating includes heating to a target temperature preferably in the range of 700-900°C, a heating rate selected from 5-10°C / min, and a heat preservation time selected from 2-3h; the second stage of step heating includes heating from the target temperature of the first stage of heating to a final temperature of 1200-1500°C; during the second stage of step heating, 100-150°C is used as a temperature step, and each temperature step is kept warm for more than 2 hours until the final temperature is reached; the heating rate is selected from 2-10°C / min, and the heat preservation time is selected from 4-6h.

4. The method for preparing the low-cost and high-safety porous silicon-carbon material according to claim 1, It is characterized in that The aniline solvent in S1 includes one or more of aniline, phenylethylamine, phenylenediamine, N-methylaniline, N-ethylaniline, N,N-dimethylaniline, and N,N-diethylaniline; preferably, the aniline solvent in S1 is preferably phenylethylamine.

5. The method for preparing the low-cost and high-safety porous silicon-carbon material according to claim 1, It is characterized in that The specific surface area of ​​the porous carbon particles in S1 is selected from 1500-2500m 2 / g, the particle size is selected from 2-10μm, and the pore size is selected from 1-5nm; the vacuum impurity removal method in S2 is to perform vacuum operation 3-5 times; the cooling method in S3 adopts a dual cooling method of air cooling and circulating water cooling; the cooling rate is selected from 60-120℃ / min.

6. The method for preparing the low-cost and high-safety porous silicon-carbon material according to claim 1, It is characterized in that The high temperature furnace in S3 is cooled to a temperature of 500-600°C; the introduction rate of the mixed gas in S3 is selected from 5-50L / min; the introduction time is selected from 4-10h; the mass ratio of acetylene and nitrogen in S3 is selected from 1:

1.

7. The method for preparing the low-cost and high-safety porous silicon-carbon material according to claim 1, It is characterized in that The reactor in S1 includes one or more of a reaction kettle, an autoclave, a stirring tank, a microwave reactor, and an ultrasonic reactor; the high-temperature furnace in S2 includes one or more of a rotary kiln, a tunnel kiln, a box furnace, a tubular furnace, and a hot air furnace; the source of the crude silicon in S2 is selected from one or more of silicon ore, silicon sand, silica, and silicon alloy.

8. A low-cost and high-safety porous silicon-carbon material, wherein the porous silicon-carbon material is obtained by the preparation method according to any one of claims 1 to 7.

9. A sodium ion battery negative electrode made of low-cost, high-safety porous silicon-carbon material. It is characterized in that The negative electrode plate is made of the low-cost and high-safety porous silicon-carbon material according to claim 8, a conductive agent and a binder.

10. A sodium ion battery, It is characterized in that The sodium ion battery comprises the negative electrode sheet, the positive electrode sheet, the separator and the electrolyte according to claim 9.